A Cross-Cultural Study of Self-Defining Memories in Chinese and American College Students - Wang, Yuening; Singer, Jefferson A. (Frontiers in Psychology, 2021)
Self-defining memories (SDMs) are touchstones in individuals’ narrative identity. This is the first SDM study to compare college students from the mainland People’s Republic of China to American college students. It examined SDMs, Big Five personality traits, and memory function in 60 students from each country (n = 120). Participants rated their memories for affect, recall frequency, and importance. Chinese students recalled their most positively rated memories more frequently and with greater importance, while American students did not show this pattern. American students who scored higher in Openness were more likely to recall negative memories. Memory content coding revealed that Chinese students recalled significantly more guilt/shame events than American students. Further analysis indicated that these memories were particularly focused on academic performance and parental expectations. The discussion suggests that follow up studies look at differing emotion regulation strategies in the two countries, as well as how the two different educational systems are affecting late adolescent identity formation processes.